Sistem Perkiraan Penggunaan Listrik Rumah Tangga Menggunakan Logika Fuzzy (Studi Kasus: PLN Area Pasuruan) - Mochamad Ali Fahmi; Muhammad Tanzil Furqon; Sutrisno Sutrisno (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In one of Indonesia's regions, Pasuruan, in recent years there has been a rapid increase in economic growth, resulting in a large increase in electricity demand to exceed the scenario originally planned by the government. The electricity system in the city of Pasuruan itself is a complex electricity system where there are difficulties in estimating the amount of electricity that can affect the readiness of the generating unit to provide electricity supply to consumers. Based on these constraints, it is necessary to estimate long-term electricity use, especially for the household sector in planning the addition of new power plants, expansion of the distribution network and planning requirements for the operation of electricity generation, so that the power generated is in accordance with load requirements. In this study Fuzzy Logic method is used to estimate or forecast. Data that were used as many as 70 historical data from January 2012 to October 2017 obtained from PLN Pasuruan Area. The results of the implementation and accuracy testing in this study got the best parameter value with the lowest MSE value of 1.602823095 and MAPE 3,84%. The test is done to get the best number of fuzzy sets at 16, while the worst value is 7 fuzzy sets.